Private Schools in Germany: Attendance up, but Not Among the Children of Less Educated Parents - Henning Lohmann; C. Katharina Spieß; Christoph Feldhaus (Weekly Report, 2009)
The percentage of children attending private school in Germany has increased sharply in recent years. According to data of the German Socio-Economic Panel (SOEP), 7% of all students now attend private school. The SOEP, which contains a range of household data, shows that the children of parents with a university entry degree ("Abitur") are more likely to attend private school than those with less educated parents. This trend has become more pronounced in recent years: between 1997 and 2007, the percentage of students with better-educated parents attending private school increased by 77%. By contrast, the corresponding increase for students with less-educated parents was only 12%. Multivariate analyses demonstrate that increasing selection in favor of better-educated groups is particularly evident at the secondary school level. At the primary school level, full-time employment of the mother and regional factors significantly increase the chances of private school attendance. Educational policy should focus on preventing children from better-educated groups from leaving the public school system. If competition among schools is to be encouraged as a matter of policy, efforts should also be made to ensure less educated families consider sending their children to private schools.
Keywords: I2; J18; 330; Private schools; Selection